Sandrine's case - Cook, Thomas H. (The Mysterious Press, an imprint of Grove/Atlantic Inc., 2013)
Samuel Madison always wondered what Sandrine saw in him. He's a meek, stuffy doctorate student, and she's a brilliant, beautiful bohemian with limitless talent and imagination. Yet on the surface their marriage seemed perfectly tranquil. Then one night Sandrine is found dead in their bed from a deadly overdose of pain medication and alcohol, and Samuel is accused of poisoning her. As the truth of their turbulent marriage comes to light, Samuel must face a town convinced of his guilt.